METODE PEMBELAJARAN BAHASA ARAB - Iliyati, Sayyidatina; Hikam, Faris Syariful (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Learning Arabic as a foreign language has been taught in various schools. Some people consider it a difficult subject. To make learning more effective and efficient, learning methods need to be well designed and implemented. The right method can improve the overall quality of Arabic language learning. In designing the method, important components to be considered include introductory activities, information delivery, student participation, tests, and follow-up activities. The selection of learning methods is based on criteria such as the orientation of the strategy to the learning task, relevance to the material, methods and techniques that are in accordance with the objectives, as well as the use of media that can stimulate students' senses. Methods often used in Arabic language learning include the grammatical-translation method, direct method, reading method, audiolingual method, and eclectic method.